Sinergi Ekonomi Lokal dan Konservasi Alam: Peran Budidaya Madu Kelulut dalam Pelestarian Hutan Adat Tukak di Desa Pangkal Niur, Bangka - Budi Darmawan; Fitri Ramdhani Harahap (Yayasan Literasi Sains Indonesia, 2026)
Stingless bee honey cultivation in Pangkal Niur Village, Bangka Regency, has demonstrated strong potential to improve local livelihoods while supporting the conservation of the Tukak Customary Forest. Covering approximately 275 hectares, the Tukak Customary Forest serves as a natural habitat for stingless bees and provides a vital nectar source for honey production. This study aims to examine how stingless bee farming contributes to community economic development while maintaining the sustainability of customary forest resources. The research adopts a qualitative case study approach, with data collected through in-depth interviews with key informants, participatory observation at cultivation sites, and relevant documentation. The findings indicate that stingless bee honey farming generates significant economic benefits for local residents, offering relatively stable income despite fluctuating weather conditions. Beyond economic gains, the activity strengthens social networks within the community, fosters social cohesion, and reinforces collective responsibility for forest protection. However, several challenges remain, including threats from natural predators such as monkeys that damage hives, as well as limited cultivation areas, which currently cover only about one hectare of the total forest area. Addressing these challenges requires careful planning, including appropriate zoning and enhanced production capacity through targeted technical training and support from government agencies and related institutions. With improved management, stingless bee honey cultivation can continue to develop as a sustainable economic activity while providing long-term benefits for both the Pangkal Niur community and the preservation of the Tukak Customary Forest.